Intersekcionální perspektiva zkoumání dopadů krize na životní dráhy v ČR: gender, třída, věk (a rodičovství) - Alena Křížková; Lenka Formánková (Gender a Výzkum)
The intersectional perspective represents, in Czech sociology, an untapped opportunity to examine the interaction between the different lines of inequality in the process of constantly changing social structure. This article aims to enrich current Czech sociological research in two ways. Firstly, it analyses and describes the impacts of the economic crisis on labour market relations in the Czech Republic. Secondly, it applies the intersectional perspective in a quantitative analysis of structural inequalities. In this perspective, we analyse the changing structure of the labour market between 2008 and 2012 at the intersection of gender, class (education), age and parenthood, using statistical indicators. Moreover, we use event-history analysis to capture the risk of job loss in the first phase of the crisis (2008–2010). Our analysis shows that the economic crisis deepened existing inequalities in the labour market, further differentiated female labour market prospects by educational attainment, especially in interaction with parenthood, and also rapidly deteriorated the labour market situation of men with low education, including fathers of small children.